2006
DOI: 10.1897/04-671r.1
|View full text |Cite
|
Sign up to set email alerts
|

Ambient copper concentrations in agricultural and natural European soils: An overview

Abstract: Copper concentrations in soil are affected by a large number of processes related to the natural spatial variability (geochemistry), the amount released, the spatial and temporal distributions of these releases, and the large number of transportation, complexation, and dissolution processes. The present study reports the generated country-specific and land use-specific environmental concentration distributions of ambient copper exposure levels in European soils that were used for the derivation of "reasonable … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 12 publications
0
26
0
Order By: Relevance
“…With their adaptation mechanisms to different stressors, including metal tolerance, and their involvement in nutrient cycles [1,5,12], fungi are of ecological relevance. In the present study, Cu, one main metallic contaminant in soils from agrosystems, was tested [18][19][20]. The originality of the present study was in testing the impact of Cu on enzymatic equipment according to the fungal physiological state.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With their adaptation mechanisms to different stressors, including metal tolerance, and their involvement in nutrient cycles [1,5,12], fungi are of ecological relevance. In the present study, Cu, one main metallic contaminant in soils from agrosystems, was tested [18][19][20]. The originality of the present study was in testing the impact of Cu on enzymatic equipment according to the fungal physiological state.…”
Section: Discussionmentioning
confidence: 99%
“…Copper has been retained because it is a common contaminant of soils from many agrosystems, amounting to 100 to 1,000 ppm (mg/kg of soil), whereas geochemical values in noncontaminated soils are between 5 and 30 ppm [18][19][20]. Two main families of enzymes involved in terrestrial ecosystem functioning were monitored: hydrolases (b-glucosidase, N-acetyl-b-glucosaminidase, b-galactosidase, acid and alkaline phosphatases, and aryl-sulfatase) and oxidoreductases (laccase, manganese and lignin peroxidases) in liquid cultures of T. versicolor.…”
Section: Introductionmentioning
confidence: 99%
“…As a point of comparison for the marine Ni HC5 values derived in the current study, ambient Ni concentration data for European marine waters were identified. Heijerick and Van Sprang () compiled ambient Ni concentration data for estuarine and estuarine‐influenced coastal waters, as well as for open marine waters and the Baltic Sea (given its semi‐enclosed conditions and brackish properties). Data from estuaries with anthropogenic point sources were excluded.…”
Section: Methodsmentioning
confidence: 99%
“…Data from estuaries with anthropogenic point sources were excluded. Following guidance from the TGD, Heijerick and Van Sprang () derived reasonable worst‐case (RWC) ambient Ni concentrations of 3.34, 0.30, and 0.79 μg/L for estuarine and estuarine‐coastal waters, open marine waters, and the Baltic Sea, respectively, which were calculated as the 90th percentile of the ambient Ni data compiled for each of these categories of water bodies.…”
Section: Methodsmentioning
confidence: 99%
“…The current copper concentration in European agricultural soil is about 31 mg/kg DM, with a range between 16 and 58 mg/kg DM (Heijerick et al, 2006). Therefore the copper concentration in copperloaded soil investigated by Berg et al (2005) was higher than the current concentrations in soil.…”
Section: Copper In Soil and Development Of Antimicrobial Resistance Omentioning
confidence: 81%